Occurrence of Purpureocillium lilacinum in citrus black fly nymphs - Medeiros, Fabiola Rodrigues [UNESP]; Santos de Lemos, Raimunda Nonata; Costa Rodrigues, Antonia Alice; Batista Filho, Antonio; Machado Gois de Oliveira, Leonardo de Jesus; Gusmao Araujo, Jose Ribamar (Soc Brasileira Fruticultura, 2018)
Black fly is a pest of Asian origin that causes direct and indirect damages to citrus, damaging the development and production of plants. For the development of efficient management strategies of the pest, the integration of control methods is necessary, and biological control is the most appropriate. Among the agents that can be used, entomopathogenic fungi arc considered one of the most important and wide-ranging use. This work investigated the occurrence of Purpureocillium lilacinum (Thom.) Luangsa-ard et al. (= Paecilomyces lilacinus), attacking nymphs of citrus black fly, Aleurocanthus woglumi Ashby (Hemiptera: Aleyrodidae). The fungus was isolated from infected Black fly nymphs, present on Citrus spp leaves in flic municipality of Morros, Maranhao. After isolation, purification and morphological and molecular characterization, pathogenicity test was performed with A. woglumi nymphs. Morphological and molecular correspondence was verified between inoculum and the reisolated, proving the pathogenicity of A lilacinum.
Keywords: biological control; Aleurocanthus woglumi; entomopathogenic; fungi